# If \[\dfrac{{10 - 3x}}{{5 + 2x}} = \dfrac{m}{n}\]; make x as the subject of the formula. Hence, find the value of x, if 3m - 4n = 2 and n = 2.5.

(a). \[x = \dfrac{{5(2n - m)}}{{2m + 3n}}\] and \[x = \dfrac{{10}}{{31}}\]

(b). \[x = \dfrac{{2(2n - m)}}{{7m + 9n}}\] and \[x = \dfrac{1}{{21}}\]

(a). \[x = \dfrac{{7(n - m)}}{{2m + n}}\] and \[x = \dfrac{{11}}{{14}}\]

(a). \[x = \dfrac{{12(n - m)}}{{2m + 3n}}\] and \[x = \dfrac{{12}}{{31}}\]

Last updated date: 19th Mar 2023

•

Total views: 304.5k

•

Views today: 7.84k

Answer

Verified

304.5k+ views

Hint: Solve the given equation to find x in terms of m and n. Then, solve for m and n from the given equations and find them. Then, substitute these values of m and n in the given equation to solve and find x.

Let us represent x in terms of m and n, starting from the given equation.

\[\dfrac{{10 - 3x}}{{5 + 2x}} = \dfrac{m}{n}\]

Cross-multiplying, we get:

\[n(10 - 3x) = m(5 + 2x)\]

Multiplying m and n inside the bracket, we get:

\[10n - 3nx = 5m + 2mx\]

Gather all terms containing x on the left-hand side of the equation to get as follows:

\[ - 2mx - 3nx = 5m - 10n\]

Now, take x as a common term from the left-hand side of the equations:

\[x( - 2m - 3n) = 5m - 10n\]

Solve for x to get as follows:

\[x = \dfrac{{5m - 10n}}{{ - 2m - 3n}}\]

Now take 5 as common term from the numerator to get:

\[x = \dfrac{{5(m - 2n)}}{{ - 2m - 3n}}\]

Now multiply numerator and denominator by -1 to get the final expression.

\[x = \dfrac{{5(2n - m)}}{{2m + 3n}}..........(1)\]

Given that, n = 2.5, substitute it in the equation 3m – 4n =2 to find the value of m.

\[n = 2.5..........(2)\]

\[3m - 4(2.5) = 2\]

\[3m - 10 = 2\]

Take 10 to the other side and add it with 2 to get 12.

\[3m = 2 + 10\]

\[3m = 12\]

Solve for m as follows:

\[m = \dfrac{{12}}{3}\]

Simplifying to obtain the value of m.

\[m = 4...........(3)\]

Substitute equation (3) and equation (2) in equation (1) to get as follows:

\[x = \dfrac{{5(2(2.5) - 4)}}{{2(4) + 3(2.5)}}\]

\[x = \dfrac{{5(5 - 4)}}{{8 + 7.5}}\]

\[x = \dfrac{5}{{15.5}}\]

Multiply numerator and denominator by 2 to obtain the final expression.

\[x = \dfrac{5}{{15.5}} \times \dfrac{2}{2}\]

\[x = \dfrac{{10}}{{31}}\]

Hence, the correct answer is option (a).

Note: Even though the ratio of m and n is represented as a function of x, we can solve them to find the value of x in terms of m and n. Don’t confuse yourself with the phrase “make the subject of the equation”, it just means express x explicitly.

__Complete step-by-step answer:__Let us represent x in terms of m and n, starting from the given equation.

\[\dfrac{{10 - 3x}}{{5 + 2x}} = \dfrac{m}{n}\]

Cross-multiplying, we get:

\[n(10 - 3x) = m(5 + 2x)\]

Multiplying m and n inside the bracket, we get:

\[10n - 3nx = 5m + 2mx\]

Gather all terms containing x on the left-hand side of the equation to get as follows:

\[ - 2mx - 3nx = 5m - 10n\]

Now, take x as a common term from the left-hand side of the equations:

\[x( - 2m - 3n) = 5m - 10n\]

Solve for x to get as follows:

\[x = \dfrac{{5m - 10n}}{{ - 2m - 3n}}\]

Now take 5 as common term from the numerator to get:

\[x = \dfrac{{5(m - 2n)}}{{ - 2m - 3n}}\]

Now multiply numerator and denominator by -1 to get the final expression.

\[x = \dfrac{{5(2n - m)}}{{2m + 3n}}..........(1)\]

Given that, n = 2.5, substitute it in the equation 3m – 4n =2 to find the value of m.

\[n = 2.5..........(2)\]

\[3m - 4(2.5) = 2\]

\[3m - 10 = 2\]

Take 10 to the other side and add it with 2 to get 12.

\[3m = 2 + 10\]

\[3m = 12\]

Solve for m as follows:

\[m = \dfrac{{12}}{3}\]

Simplifying to obtain the value of m.

\[m = 4...........(3)\]

Substitute equation (3) and equation (2) in equation (1) to get as follows:

\[x = \dfrac{{5(2(2.5) - 4)}}{{2(4) + 3(2.5)}}\]

\[x = \dfrac{{5(5 - 4)}}{{8 + 7.5}}\]

\[x = \dfrac{5}{{15.5}}\]

Multiply numerator and denominator by 2 to obtain the final expression.

\[x = \dfrac{5}{{15.5}} \times \dfrac{2}{2}\]

\[x = \dfrac{{10}}{{31}}\]

Hence, the correct answer is option (a).

Note: Even though the ratio of m and n is represented as a function of x, we can solve them to find the value of x in terms of m and n. Don’t confuse yourself with the phrase “make the subject of the equation”, it just means express x explicitly.

Recently Updated Pages

If abc are pthqth and rth terms of a GP then left fraccb class 11 maths JEE_Main

If the pthqth and rth term of a GP are abc respectively class 11 maths JEE_Main

If abcdare any four consecutive coefficients of any class 11 maths JEE_Main

If A1A2 are the two AMs between two numbers a and b class 11 maths JEE_Main

If pthqthrth and sth terms of an AP be in GP then p class 11 maths JEE_Main

One root of the equation cos x x + frac12 0 lies in class 11 maths JEE_Main

Trending doubts

What was the capital of Kanishka A Mathura B Purushapura class 7 social studies CBSE

Difference Between Plant Cell and Animal Cell

Write an application to the principal requesting five class 10 english CBSE

Ray optics is valid when characteristic dimensions class 12 physics CBSE

Give 10 examples for herbs , shrubs , climbers , creepers

Tropic of Cancer passes through how many states? Name them.

Write the 6 fundamental rights of India and explain in detail

Write a letter to the principal requesting him to grant class 10 english CBSE

Name the Largest and the Smallest Cell in the Human Body ?